Assessing Country’s Reliance on Renewable Energy through Energy Profile and Political Economy Aspects: A Cross Countries Study from 1990 to 2012 - Paramitha, Santi Hapsari; Hidayat, Nurman (Global: Jurnal Politik Internasional, 2017)
This study examines the relationship between country’s reliance on renewable energy, energy profile, and political economy aspects using dynamic panel data models for a global panel consisting of 43 countries. The time component of our dataset is 1990-2012 inclusive. To make the observation more specific, this study investigates the relationship of a number of sub-samples which are constructed based on the region where the countries belong. In this way, this study ends up with several region samples; namely Western, Asia, Middle East (ME), Africa, Commonwealth of Independent States (CIS), and Latin America. In the empirical part, this study performs a region-based analysis to capture any variations and logical explanation behind them. The results suggest that dependency on oil import, engagement on international environment agreement, economic development, and country size country’s reliance on renewable energy are among the factors that are statistically significant to influence country’s adoption of renewable energy.